ROCK inhibitor modified intraocular lens as an approach for inhibiting the proliferation and migration of lens epithelial cells and posterior capsule opacification. (7th August 2019) - Lin, Lei; Lin, Quankui; Li, Jin; Han, Yuemei; Chang, Pingjun; Lu, Fan; Zhao, Yun-e
Abstract : ROCK pathway plays a critical role in the lens epithelial cell migration and proliferation through cytoskeleton remodeling, and the established ROCK inhibitor modified intraocular lens can prevent posterior capsule opacification formation. Abstract : Lens epithelial cells (LECs) in the capsule play a critical role in posterior capsule opacification (PCO) formation following cataract surgery. Cytoskeleton remodeling and the related ROCK pathway are quite important during cell migration and proliferation, but their role in LECs is still unclear. This study aimed to explore the mechanism of the ROCK pathway in the behavior of LECs and established a drug modified IOL for PCO prevention. We observed that the ROCK pathway inhibitor (Y27632) or cofilin knockdown reduced HLEC-B3 migration and proliferation. Furthermore, we revealed that cofilin could regulate the migration and proliferation of LECs through its phosphorylation. Interestingly, the capping protein CAPZA1 and ERM family also had an effect on the behavior of LECs. In addition, we established Y27632-PLGA modified IOLs, implanted them into rabbit eyes and found them to exhibit good safety and biocompatibility in vivo . Moreover, satisfying PCO prevention results were observed at 28 days post-operation. In summary, the ROCK pathway and the cytoskeleton remodeling protein regulate cell migration and proliferation, and the Y27632-PLGA modified IOL can prevent PCO formation.